IMPLEMENTATION OF E-COURT IN THE RELIGIOUS COURT OF PONTIANAK CITY - Oktavia, Anisa; Sari, Imas Komala; Anisa, Kholifatun (Tanjungpura Legal Review, 2022)
To face the era of very rapid globalization, the legal world is also required to make changes and new innovations.Therefore, the online system is a new breakthrough in the administration of justice.By utilizing the sophistication of technology in the form of an internet network, it can create a system in forming an application called E-Court.The purpose of this study was to determine the implementation of the E - Court in the case settlement process at the Religious Courts of Pontianak City.This research is a qualitative research method with descriptive analysis research method.   the implementation of the E - Court at the Pontianak City Religious High Court has not been fully effective .   This can be seen from the number of E - Court users who are not too many including other users .   The main cause of this system being ineffective is due to the ignorance of the community plus the people's low interest in reading, as well as the unpreparedness of the community to face technological developments, where they are not ready and not accustomed to conducting an IT-based court system.